2021
DOI: 10.1021/acs.iecr.1c00353
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up Study on the Performance of the Asymmetric Rotating Impeller Extraction Column

Abstract: In the present work, hydrodynamics and mass transfer performance of the asymmetric rotating impeller column (ARIC) of different scales, that is, ARIC 1 (I.D. = 0.1 m), ARIC 2 (I.D. = 0.22 m), and ARIC 3 (I.D. = 0.3 m), have been investigated. The liquid−liquid system used in the present study is phosphoric acid containing metal ions and the organo-phosphorous solvent. The effect of different operating conditions on regime transition in ARIC of different scales has been analyzed. Correlations have been develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…q p e 2.5 (13) Various drag models are investigated in the present study, and a comparison between experimental and simulated results has been made. In liquid−liquid dispersions, multiple factors affect the drag coefficient.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…q p e 2.5 (13) Various drag models are investigated in the present study, and a comparison between experimental and simulated results has been made. In liquid−liquid dispersions, multiple factors affect the drag coefficient.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…However, the current universal drag models do not account for these parameters. 13 The dependency of the drag coefficient on the volume fraction was analyzed for the various models. In the present study, simulations were conducted to examine the influence of various drag models, such as Universal, Schiller−Naumann, Ishii−Zuber, and Kumar−Hartland, on the holdup distribution in a stirred tank.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22] In ADM, the product of mass transfer coefficient and interfacial area is simplified as a constant through the height of the column. 23 However, experimental results have demonstrated that the dispersed phase holdup and drop size in contactors vary significantly along the column height, 3,[24][25][26] which not only leads to a longitudinal variation of specific interfacial area but also affects axial distribution of the mass transfer coefficient. 27 Consequently, more reliable theoretical methods for predicting mass transfer behavior are needed in the designing and scaling-up of such extractors.…”
mentioning
confidence: 99%